2013
DOI: 10.3233/jad-2012-121603
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Surpasses Cerebrospinal Fluid as Predictor of Cognitive Decline and Medial Temporal Lobe Atrophy in Subjective Cognitive Impairment and Mild Cognitive Impairment

Abstract: Neuropathological correlates of Alzheimer's disease (AD) emerge years before dementia. Biomarkers preceding cognitive decline and reflecting the causative processes can potentially aid early intervention and diagnosis. Diffusion tensor imaging (DTI) indirectly reflects tissue microstructure. To answer whether DTI is an early biomarker for AD and to explore the relationship between DTI and the established biomarkers of medial temporal lobe atrophy and cerebrospinal fluid (CSF) Aβ(42), T-tau, and P-tau, we longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
90
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 53 publications
8
90
0
1
Order By: Relevance
“…Regional diffusion measures of white matter integrity, most notably of the fornix, posterior cingulum, and parahippocampal white matter, have also shown promising accuracies between 77% and 95% for the prediction of conversion from MCI to AD dementia over clinical follow-up times of 2 to 3 years Mielke et al, 2012;Scola et al, 2010;Selnes et al, 2013). Preliminary findings further suggest that MD may be of higher predictive value compared to FA , and that diffusion metrics may be generally better predictors of conversion than volumetric measurements on structural MRI (Fellgiebel et al, 2006;Scola et al, 2010), particularly for the prediction of future cognitive impairments in cognitively normal elderly (Fletcher et al, 2013;Zhuang et al, 2012).…”
Section: Contribution Of Multimodal Imaging Of Connectivity To Diagnomentioning
confidence: 99%
“…Regional diffusion measures of white matter integrity, most notably of the fornix, posterior cingulum, and parahippocampal white matter, have also shown promising accuracies between 77% and 95% for the prediction of conversion from MCI to AD dementia over clinical follow-up times of 2 to 3 years Mielke et al, 2012;Scola et al, 2010;Selnes et al, 2013). Preliminary findings further suggest that MD may be of higher predictive value compared to FA , and that diffusion metrics may be generally better predictors of conversion than volumetric measurements on structural MRI (Fellgiebel et al, 2006;Scola et al, 2010), particularly for the prediction of future cognitive impairments in cognitively normal elderly (Fletcher et al, 2013;Zhuang et al, 2012).…”
Section: Contribution Of Multimodal Imaging Of Connectivity To Diagnomentioning
confidence: 99%
“…25 Our population-based study revealed that reduced microstructural white matter integrity was also predictive of subsequent cognitive decline, independent of WMH load. Although previous research has suggested that reduced microstructural white matter integrity in aging is largely explained by WMH, 26 our data indicated that the association between reduced white matter integrity and cognitive decline could not be accounted for by global WMH load.…”
mentioning
confidence: 99%
“…We have previously shown that DTI is a better predictor of cognitive decline than CSF biomarkers in subjects with SCD and MCI. 13 Four common DTI indices are derived, likely reflecting different microstructural properties, fractional anisotropy (FA), mean diffusivity (MD), radial diffusivity (DR), and axial diffusivity (DA). Although the neurobiological interpretation of the DTI indices is complex, increased DR is thought to reflect changes to axonal diameter, axonal density and myelination, while DA has been associated with the axonal integrity.…”
Section: Introductionmentioning
confidence: 99%